In situ response of Nostoc commune s.l. colonies to desiccation in Central Svalbard, Norwegian High Arctic - Kvíderová, J. (Jana); Elster, J. (Josef); Šimek, M. (Miloslav) (2011)
The effects of desiccation on photochemical processes and nitrogenase activity was evaluated in Nostoc commune s.l. colonies from a wet thufur meadow in Svalbard. The colonies were subjected to slow desiccation at low temperature and low irradiance and the protochemical processes were measured using variable chlorophyll fluorescence and the nitrogenase activity using acetylene-ethylene reduction assay. No changes in colony shape was observed till the colony lost 30% of its fully-hydrated state weight (original weight) and such partly-hydrated state could be even beneficial due to better difusion of CO2 and N2 into cells. Even loss of 50% of the original weight did not affect the metabolical processes. The nitrogeanse activity was not detectable when the colony lost 80 % of its original weight and the photochemistry ceased when the colony lost more than 90 % of its original weight indicating thus good adaptation to water fluctuation and desiccation in situ.